Profile of sulphacetamide pharmacokinetics on uranyl nitrate-induced renal failure rats - Djoko Wahyono; Arief Rahman Hakim; Agung Endro Nugroho (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2007)
Kidney is a vital organ which has main function to maintain the body homeostasis. The role of kidney is the excretion (elimination) of waste product, and if there is pathologically a renal failure so will change the drug pharmacokinetics and in turn change it’s potency. The present study evaluated the effect of uranyl nitrate-induced renal failure on the pharmacokinetics profiles of sulphacetamide in rats.The study was conducted by employing a completely randomized design in male Wistar in bred rat (aged 2-2.5 months, 150-250 g). The animals in group I were given sulphacetamide sodium with an oral single dose 100.0 mg/kg BW (control group) and in group II were given pretreatment with uranyl nitrate at 3 days before sulphacetamide administration.After collected at some certain times, the drug concentrations on bloods were analyzed by an ultraviolet spectrophometer. The results have shown that uranyl nitrate-induced renal failure decreased the primer pharmacokinetics parameter i.e. total clearance (ClT) and volume of distribution in steady state (Vdss), significantly (P<0.05). The decreasing of these parameter could cause alteration of the secondary pharmacokinetics parameters of sulphacetamide and these derivates i.e. Cmax, tmax, AUC0-240, AUC0-inf, MRT, K and t1/2 elimination significantly (P<0.05). According from the results, it is concluded that uranyl nitrate-induced renal failure affected the pharmacokinetics of sulphacetamide or could increase the sulphacetamide concentration in blood.Key words : sulphacetamide, pharmacokinetics, renal failure, uranyl nitrate